Antioxidant Potential of Bark Extracts from Boreal Forest Conifers - Jean Legault; Karl Girard-Lalancette; Dominic Dufour; André Pichette (MDPI AG, 2013)
The bark of boreal forest conifers has been traditionally used by Native Americans to treat various ailments and diseases. Some of these diseases involve reactive oxygen species (ROS) that can be prevented by the consumption of antioxidants such as phenolic compounds that can be found in medicinal plants. In this study, ultrasonic assisted extraction has been performed under various solvent conditions (water:ethanol mixtures) on the bark of seven boreal forest conifers used by Native Americans including: Pinus strobus, Pinus resinosa, Pinus banksiana, Picea mariana, Picea glauca, Larix laricina, and Abies balsamea. The total phenolic content, as well as ORACFL potency and cellular antioxidant activity (IC50), were evaluated for all bark extracts, and compared with the standardized water extract of Pinus maritima bark (Pycnogenol), which showed clinical efficiency to prevent ROS deleterious effects. The best overall phenolic extraction yield and antioxidant potential was obtained with Picea glauca and Picea mariana. Interestingly, total phenolic content of these bark extracts was similar to Pycnogenol but their antioxidant activity were higher. Moreover, most of the extracts did not inhibit the growth of human skin fibroblasts, WS1. A significant correlation was found between the total phenolic content and the antioxidant activity for water extracts suggesting that these compounds are involved in the activity.